The role of problem-solving ability among halal entrepreneurs’ startups in Brunei Darussalam - Khairul Hidayatullah Basir; Raihana Mohd Raffi; Hafini Mahmud; Najihah Hanisah Marmaya (Majmuah Enterprise, 2022)
The paper aims to investigate problem-solving ability of startups in Brunei Darussalam during their business pitching. The purpose of the paper is therefore to assist prospect startups to tap into halal market. The researchers collected the data through in-depth individual interviews with the selected experienced panels judges of business pitching or business plans from different organisations. The findings show that the concept of halal entrepreneurship is still subjective andthere is still an issue of copy and paste business idea. Prospect halal entrepreneurs should experience the international market and engage with industrial experts in order for them to identifythe potential and niche market in halal industry in Brunei. This will also help them to enhance their problem-solving ability. In order to ensure sustainability of their business, market validation is very important to be done. The significance of this paper is to promote the growth of startups in more diversified areas and involvement of youth in the halal industry through their problem solving ability. The limitation of this paper is it present only preliminary findings and empirical studies needto be done to prove the connection between problem solving ability, opportunity recognition and innovative behaviour